Development of Student Worksheet on Acid Base Matter Based on Chemistry Representation and Chemistry Literay to Train Student Critical Thinking Skill for Senior High School Grade XI (UNESA Journal of Chemical Education, 2018)
This study purposed to describe feasibility of student worksheet based on chemistry representation and chemistry literacy to train student critical thinking skills on acid base matter. This study used research and development method according to ADDIE model. Step of ADDIE model includes analysis, design, development, implementation, and evaluation. The instrument of this study used student worksheet assessment, quality student worksheet assessment, critical thinking test, student questionnaire and activity observation sheets. The subject of this study consist of chemistry lecturer, one chemistry teacher and 15 students grade XI of SMA Khadijah which chosen heterogeneously. The results showed that (1) Student worksheet was developed that evaluated on feasibility category with average percentage of contents, presentation, graphic and linguistic respectively 90,86% (very feasible), 90,34% (very feasible), 91,66% (very feasible) and 91,11% (very feasible). (2) Student critical thinking skills of worksheet on each indicator perspectively obtained between 77,6% – 95,6% on interpretation, 78,66% - 89,3% on analysis, 79,1% - 92% on evaluation, 66,67% - 82,6% on explanation and 81,33% - 94,6% on inference indicator. (3) Student respon obtained percentage between 80% - 91,67% in very good category, its supported by relevant student activity (critical thinking) between 96,67% - 98,67%. It showed that student’s critical thinking skills in every indicator on critical until very critical category. Based on the data result indicate that worksheet is declared feasible to trill critical thinking skill to material of acid-base theory. keywords: chemistry representation, chemistry literacy, critical thinking skills, acid base theory.